MEK-independent ERK activation in human neutrophils and its impact on functional responses. Issue 4 (4th August 2015) - Simard, Francois A; Cloutier, Alexandre; Ear, Thornin; Vardhan, Harsh; McDonald, Patrick P
Abstract : Therapeutic strategies based on MEK inhibition may require complementation of ERK inhibition in chronic inflammatory conditions featuring a strong neutrophilic component. Abstract: Neutrophils influence innate and adaptative immunity, notably through the generation of numerous cytokines and chemokines and through the modulation of their constitutive apoptosis. Several signaling cascades are known to control neutrophil responses, including the MEK pathway, which is normally coupled to ERK. However, we show here that in human neutrophils stimulated with cytokines or TLR ligands, MEK and ERK are activated independently of each other. Pharmacological blockade of MEK had no effect on the induction of ERK kinase activity and vice versa. In autologous PBMC exposed to the same stimuli or in neutrophils exposed to chemoattractants, this uncoupling of MEK and ERK was not observed. Whereas we had shown before that MEK inhibition impairs cytokine generation translationally in LPS- or TNF-stimulated neutrophils, ERK inhibition affected this response transcriptionally and translationally. Transcriptional targets or ERK include the mitogen- and stress-activated protein kinase 1 (MSK-1) and its substrates, C/EBPβ and CREB, whereas translational targets include the S6 kinase and its substrate, the S6 ribosomal protein. In addition to affecting cytokine production, ERK inhibition interfered with how LPS or TNF promotes neutrophil survival and levels of the myeloid cell leukemia 1 (Mcl-1) antiapoptotic protein. Whereas the ERK-activating kinase was not identified, we found that the MAP3K, TGF-β-activated kinase 1 (TAK1), acts upstream of ERK and MEK in neutrophils. Our results document a functional uncoupling of the MEK/ERK module under certain stimulatory conditions and suggest that therapeutic strategies based on MEK inhibition might benefit from being complemented by ERK inhibition, particularly in chronic inflammatory conditions featuring a strong neutrophilic component.